"Wchodzimy w pociągi, by wysiąść gdziekolwiek" - kolejowe inspiracje w twórczości Karola Graczyka - Szott, Mirosława (1987- ) (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Travelling by train is one of the most visible inspirations in the works of Karol Graczyk. The motif appears in his poetry, prose, and in the title of the online journal "PKPZin" edited by him. How does Graczyk show the specific space of the train and the railway station? Why does he only travel second class and why is that means of transportation an important place for him, rather than just a link between distant points on the map?
Keywords: koleje; przestrzeń; dworzec kolejowy; pociągi; relacje międzyludzkie; Graczyk, Karol (1984 -); railways; space; trains; station; human relationships